The secret garden - Burnett, Frances Hodgson, 1849-1924.; Rust, Graham (Boston, MA : D.R. Godine, 1986)
Ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden.
Keywords: Orphans -- Fiction; Gardens -- Fiction; People with disabilities -- Fiction; Yorkshire (England) -- Fiction